Preparation, characterization and spectroscopy of the europium diphenylphosphinate complex - Stucchi, Elizabeth B.; Scarpari, Sérgio L.; Couto Dos Santos, Marcos A.; Leite, Sérgio R. A. (Elsevier, 1998)
The purpose of this work is to study the preparation and spectroscopic behavior of the europium diphenylphosphinate complex -Eu(DPP)3. Elemental and thermogravimetric analysis, powder X-ray diffractometry, and infrared spectroscopy were applied to characterize the formula of the final product and the sixfold coordination of the Eu3+ ion. Excitation and emission spectra have been recorded at liquid nitrogen and room temperatures. The 5D0→7F2 transition intensity decreases when T decreases in comparison to the 5D0→7F1 transition intensity. Molecular mechanic calculations were developed in order to obtain the spatial coordinates of the Eu3+ and ligand ions. The simple overlap model was used to calculate the total splitting of the 5D0→7F1 transition, 5D0→7F0/5D 0→7F2 ntensity ratio and the intensity parameters, Ωλ (λ=2 and 4). Good agreements between theoretical predictions and experimental results have been obtained with g=2/3 as the effective charge and α=0.8×10-24 cm3 as the isotropic polarizability of the oxygen. © 1998 Elsevier Science S.A.
Keywords: Europium diphenylphosphinate complex; Intensity parameters; Luminescence; UV-Vis-IR spectroscopy; Computer simulation; Electron transitions; Infrared spectroscopy; Luminescence of solids; Mathematical models; Molecular dynamics; Molecular structure; Thermogravimetric analysis; Ultraviolet spectroscopy; X ray powder diffraction; Europium diphenylphosphinate; Europium compounds